Premature ovarian ageing following heterozygous loss of Senataxin. (18th December 2020) - Subramanian, G N; Lavin, M; Homer, H A
Abstract: Premature loss of ovarian activity before 40 years of age is known as primary ovarian insufficiency (POI) and occurs in ∼1% of women. A more subtle decline in ovarian activity, known as premature ovarian ageing (POA), occurs in ∼10% of women. Despite the high prevalence of POA, very little is known regarding its genetic causation. Senataxin (SETX) is an RNA/DNA helicase involved in repair of oxidative stress-induced DNA damage. Homozygous mutation of SETX leads to the neurodegenerative disorder, ataxia oculomotor apraxia type 2 (AOA2). There have been reports of POI in AOA2 females suggesting a link between SETX and ovarian ageing. Here, we studied female mice lacking either one ( Setx +/− ) or both ( Setx −/− ) copies of SETX over a 12- to 14-month period. We find that DNA damage is increased in oocytes from 8-month-old Setx +/− and Setx −/− females compared with Setx +/+ oocytes leading to a marked reduction in all classes of ovarian follicles at least 4 months earlier than typically occurs in female mice. Furthermore, during a 12-month long mating trial, Setx +/− and Setx −/− females produced significantly fewer pups than Setx +/+ females from 7 months of age onwards. These data show that SETX is critical for preventing POA in mice, likely by preserving DNA integrity in oocytes. Intriguingly, heterozygous Setx loss causes an equally severe impact on ovarian ageing as homozygous Setx loss. Because heterozygous SETX disruption is less likely to produce systemic effects, SETX compromise could underpin some cases of insidious POA.